Laser powder bed fusion additive manufacturing of in-situ low-alloyed steel and layer-wise phase control - Poh, Andre Zhen Yang (Nanyang Technological University, 2022)
Additive Manufacturing (AM) is a process where an object is constructued layer by layer, compared to conventional subtractive technologies. One such technique is the Laser Powder Bed Fusion (LPBF), also known as industrial 3D printing. Some of the main advantages of LPBF are the freedom in design and minimization of waste. Due to the way the object is constructed, it is common to have anisotropic microstructural properties in the direction of building. The complex thermal history of LPBF also reduces the available materials used for printing. The project focuses on a AISI 8620 low alloy steel, where different phases such as ferrite, austenite and martensite can exist. Through the use of focused laser beams and controlled pausing, we aim to locally tune the microstructure to create a heterogeneous structure with improved magnetic and mechanical properties.